A comparison of vertical structural types in the railway industry: A simple mathematical explanation model. (September 2020) - Mizutani, Fumitoshi
Abstract: This study explores how different types of vertical structure affect the cost of rail organizations. Three types of vertical structure are considered: vertical separation, intermediate organizations, and vertical integration. We focus on the competition factor and managerial factors. A series of our analyses show the following major findings. First, the cost advantageous vertical structure can be explained by the degree of train density. At smaller (larger) train density, vertical separation (integration) is best. At medium train density, an intermediate organization is best. Second, the boundaries distinguishing advantageous vertical structure vary according to several factors. When the effects of misalignment and transaction costs increase, the boundary of organizational structures moves in the smaller train density direction (i.e. the vertical separation side). This means that the range of vertical integration becomes larger. On the other hand, when the specializing cost saving effect increases, the range of vertical separation becomes larger, as the boundary of organizational structures moves in the larger train density direction (i.e. the vertical integration side). Last, the competition effect on the boundary shows no concrete result. This means that the cost advantageous range of vertical separation or vertical integration varies according to the degree of competition and other factors.